120 CYTOKINE RECEPTOR GP130 SIGNALING STIMULATES SECRETION OF TISSUE FACTOR-EXPRESSING TUMOR MICROPARTICLES FROM CANCER CELLS. Issue 1 (1st January 2007) - de Idiáquez, D. A.; Branam, D.; Selander, K. S.; Chen, D.; Teng, L.; Merrell, M.; Rose-John, S.; Sheehan, J.; Harris, K. W.
Abstract : The cytokine receptor gp130 is the common signaling subunit for the interleukin (IL)-6 family of inflammatory mediators. We have previously shown that inhibition of gp130 via a dominant negative (DN) protein blocks angiogenesis in an animal model of invasive breast cancer. We describe here the results of a genomic screen that defines a panel of genes whose expression is significantly affected by DN gp130. These genes are involved in processes such as matrix remodeling and angiogenesis. For instance, tissue factor (TF) expression is decreased in both cell lysates and secreted tumor microparticles from MDA-231 cells expressing DN gp130 protein. TF and tumor microparticles have both been shown to be involved in tumor invasion and angiogenesis. Functionally distinct populations of microparticles have been described based on size and molecular composition. We have separated MDA-231 microparticles into two size fractions based on differential centrifugation and examined them by ELISA for TF. The 21, 000 × g microvesicle (MV) fraction was found to have a concentration of TF sixfold greater than the 100, 000 × g exosome fraction. The tumor MV from control cells were threefold more invasive than DN gp130 MV in a Matrigel invasion assay. These results identify a novel biologic consequence of inflammatory signaling on important mediators of tumor invasion and angiogenesis. TF-expressing tumor MV may represent therapeutic targets and/or clinically useful plasma biomarkers.